Outcomes of heart-lung transplantation in Eisenmenger syndrome compared to primary pulmonary hypertension. (March 2023) - Sainathan, Sandeep; Ryan, John; Said, Sameh; Mullinari, Leonardo; Sanchez, Pablo
Objective: Heart-Lung Transplantation (HLTX) is required both in primary pulmonary hypertension (PPH) and Eisenmenger syndrome (ES) when there is associated end-stage heart disease. Although PPH is associated with an otherwise structurally normal heart, ES is associated with congenital heart defects, which may increase the complexity of the operation. This study analyzes if the diagnosis (PPH vs. ES) is related to short-term outcomes after HLTX. Methods: Patients ≥18 years of age with PPH and ES who underwent HLTX were identified in the United Network for Organ Sharing database from 2005 to 2021. Patients were propensity score matched on heart and lung listing status at the time of transplant. Univariable, multivariable, and Kaplan–Meir survival analyses were performed. Results: The unmatched cohort had 128 PPH and 44 ES patients, and the matched cohort had 44 patients in each group. PPH patients had lower waitlist times and PA pressures but higher FEV1, heart, and lung listing status and ECMO bridge. There were no differences in immediate postoperative outcomes such as dialysis, stroke, and airway dehiscence. PPH patients had a higher treatment rejection in the first year. The 30-day, 1-year, and 3-year survival were better in the PPH group. However, a landmark analysis excluding deaths within 30 days eliminated differences in survival between the groups. Post-transplant dialysis and postoperative mechanical ventilation >5 days were risk factors for 1-year mortality in ES. Conclusion: The short-term outcomes of HLTX are inferior in ES compared to PPH and much of the attrition in ES occurs in the immediate postoperative period.